Finite element modelling - Ishak, M. I. (Springer Verlag, 2013)
In this chapter, all methods involved to generate 3D finite element models are presented in detail. The finite element modelling initially started by the reconstruction of bone models and then followed by the development of implant models. The 3D anatomical model of craniofacial presented in this text was obtained by the original maxilla with a high degree of bone resorption. The simulated implantation procedure would be conducted to place the implants into bone site afterwards. The prepared models were assigned with material properties, contact parameters, boundary conditions and simulated loadings before proceeding to the analysis. The 3D FEA was then performed with the data of equivalent von Mises stress and displacements within the respective models were presented numerically and plotted in spectrum colouring scale.